Accountability and Communicative Action An Alternative Imaginary - AMITABH MUKHOPADHYAY (Economic and Political Weekly December 24, 2005, 2005)
The campaign for democratic decentralisation in Kerala was no doubt sagacious, participative and vigorously implemented. However, there was no audit certification to vouch for expenditure incurred or to counter allegations of decentralised corruption. Social audit as communicative action - drawing on the experience of the Mazdoor Kisan Shakti Sangathan in the conduct of jan sunwais (public hearings) in Rajasthan - can help foreground the pretext of accountability and unleash the energies of people to establish accountability in local bodies.